Impact of cross-border competition on the German retail gasoline market - German-Polish border - Mats P. Kahl (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2020)
Competition on the German gasoline market is of interest for economists, competition authorities and the general public alike. In this paper, I analyse how constantly lower gasoline prices in Poland affect the prices set in the German border region. More precisely, I estimate the impact of one additional kilometre of distance to the nearest Polish competitor on the price charged by German gasoline stations. The analysis is based on a complete dataset of German gasoline prices and an accurate assessment of distances. Fitting random effects models for German gasoline prices while controlling for various station characteristics, I find no evidence suggesting that German gasoline stations enter into price competition with their Polish opponents. The analysis of gasoline station infrastructure in the German border region reveals increasingly sparse gasoline station density when approaching the Polish border, along with an increasing share of premium brands. On the one hand, I find evidence suggesting that price competition between German and Polish gasoline stations is dominated by the enormous tax differences that presumably exceed profit margins by far; on the other hand, I reveal the consequences on the market structure that are caused by German gasoline stations anticipating this permanent difference in taxes when deciding upon where to locate their gasoline stations.
Keywords: L13; L41; L92; 330; gasoline market; cross-border competition; market transparency